The Influence Of Village Apparatus Competency And The Use Of Information Technology On The Accountability Of Village Fund Management In Paya Tusam Village - M. Yogi Attoriq; Junawan Junawan; Yunita Sari Rioni (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the influence of village apparatus competency and information technology utilization on accountability in village fund management in Paya Tusam Village. The research is motivated by the increasing demands for transparency and accountability in village fund management, as well as the limitations in apparatus competency and information technology utilization in village financial administration. The study uses a quantitative approach with multiple linear regression methods, with data obtained through questionnaires to Paya Tusam Village apparatus. The independent variables of the study are village apparatus competency and information technology utilization, while the dependent variable is accountability in village fund management. The results of the study are expected to provide empirical evidence regarding the influence of apparatus competency and information technology utilization in improving accountability in village fund management and serve as evaluation material for the village government in realizing transparent and accountable financial governance.